The Readiness of Education in Indonesia in Facing The Society Era 5.0 - Hikmat Hikmat (Universitas Pahlawan Tuanku Tambusai, 2022)
Technological developments have led to the rapid growth of dynamics in education transformation. Technological developments in the digital world lead to new learning systems and methods. These developments can be marked by the emergence of the determination of the era of globalization towards the era of Society 5.0. Therefore, the Indonesian state needs to see its country’s readiness to face the Society 5.0 era for its education sector. This research will use a qualitative approach and data from previous studies. The study results found that education development in the era of Society 5.0 was strongly influenced by technology. This phenomenon can help overcome educational problems during the Covid-19 pandemic because the focus is on using various technologies, so there is no need for education through traditional face-to-face methods.